Современное состояние и перспективы развития сельского хозяйства Ставропольского края - E. V. Pismennaya (Зерновое хозяйство России)
The present state and prospects of agricultural development in the Stavropol Area The article analyzes the present state and prospects of plant-breeding development, as a leading branch of the Stavropol Area that specializes on cultivation of grain and technical crops and on animal breeding. Special attention is paid on dynamics of sowing areas, gross yields and productivity of grain crops, ratio of branches and products of plant-breeding and husbandry, their profitability (unprofitability), and adaptive branch development and planning of agriculture and AIC as an unclaimed function in the system of modern state management. The article emphasizes that the objective features of the grain economy of the Stavropol Area are that no less than 70% of the arable land is located in the area of risky farming and about 65% of the total production of agricultural crops is provided by wheat, barley and other crops in the semi-arid zones. This largely determines the high natural and climatic dependence of the grain economy, the annual and regional variability of grain production, which is proved by mathematical analysis. However, the realizable market relations in the absence of a state adaptive concept of the agricultural development of the region result in misbalance and inefficiency in the industry functioning, simplification of the system of production organization of agricultural production, and agro zoning activity. The article draws the conclusions that indicate a greater dependence of plant-breeding on market conditions, the volume of capital investment and pricing, the natural resource potential of land use, and the significant deformation of the modern agricultural system.